Hubungan Pengaturan Emosi Positif Antara Citra Tubuh Dan Kualitas Hidup Pada Wanita Masa Menopause - Linda Juwita (Poltekkes Kemenkes Kupang, 2020)
Background: Post menopausal women feel that they are old, unhealthy, and no longer beautiful and this affects their body image. In some women, menopause symptoms may severely impair quality of life. The objective is is there a correlation between positive emotional management between body image and quality of life in menopausal women. Methods: This study was conducted using an analytic observational method with a cross-sectional design. The population is 68 elderly female members of the Aprilia Posyandu in the Kenjeran Community Health Center. The sample is menopausal women. The data in this study were analyzed using ordinal regression for the correlation between positive emotional management, body image and quality of life. Result: p> 0.05 positive emotional management with body image. Statistical test p <0.05 for the correlation of positive emotional management with quality of life. Conclusion: there is a correlation between positive emotional management and quality of life and there is no relationship between positive emotional management and body image. Pendahuluan: Wanita menopause merasa menjadi tua, tidak sehat, dan tidak cantik lagi dan hal ini berpengaruh terhadap citra tubuh wanita. Pada beberapa wanita, gejala-gejala menopause mungkin sangat mengganggu kualitas hidup. Tujuan yaitu adakah hubungan pengaturan emosi positif antara citra tubuh dan kualitas hidup pada wanita masa menopause. Metode: Penelitian ini akan dilakukan dengan metode observasional analitik dengan rancangan berupa cross-sectional. Populasi yaitu anggota wanita Posyandu Lansia Aprilia di wilayah kerja Puskesmas Kenjeran sebanyak 68 lansia.